Landscape with human figure - Campo, Rafael (Duke University Press, 2012)
I. Landscape with human figure -- On New Year's Day -- Nightfall in Asturias -- Quatrains for a Shrinking World -- The Blackouts -- Ghazal in a Time of War -- Outside Fayetteville -- What I Would Give -- For My Brother'sWedding -- Landscape with Human Figure -- II. Speak to me -- In Praise of Experience -- October Afternoon, 1986 -- Oysters -- Your Black Eyes -- Playing "Fidel and Peron" -- On Valentine's Day -- Last Hours in Florence -- Speak to Me -- Poem for My Familiar -- After Losing Him -- III. Afraid of the dark -- Afraid of the Dark -- IV. Undetectable Phone Messages on Call -- Undetectable Spiritual, ca. 1999 -- On Thanksgiving -- The Same Old Place -- Supernumerary Poem with Fruit Pastries that Allegorically Addresses Death -- On the Virtues of Not Shaving -- The Four Humours -- V. Questions for the Weather -- The Age-Old Problem of Sentimental Verse -- The Couple -- After the Weekly Telephone Call -- For a Dear Friend Who Is Grieving -- Love Poem Written Especially for You -- Living with Illness -- Doberman Pinscher, Dreaming -- Upon Overhearing, "Anyone CanWrite Like Elizabeth Bishop" -- You Can Just See the Cynicism -- Cuban Canticle in Five Parts -- On Christmas Eve -- The Beech Forest -- In Case of Emergency Landing -- Questions for the Weather